A contribution to the establishment of extract standards from the leaves of Clinacanthus nutans (Burm.f.) Lindau - Linh, Le Nguyen Tu; Quang Dao, Vu; Dinh Thach, Bui; Thi Ben, Trinh; Thi Linh Giang, Tran; Kim Thach, Le (Vietnam Journal of Biotechnology, 2020)
Nowadays, herbs have become a popular form of healthcare. Clinacanthus nutans (Burm.f.) Lindau (family Acanthaceae) is popular in Asia, especially in the tropical countries. Extracts of C. nutans leaves are widely used to treat diseases of skin, anti-inflammatory, anti-virus, anticancer, antioxidant, antidiabetic, immunomodulatory, wound healing and analgesic activities, etc. This study determined the parameters of ethanol extract of C. nutans leaves including pH, total weight loss due to water, total ash content, heavy metal content, microbiological limits, pesticide residual content, presence and contents of C-flavones. The C-flavones such as shaftoside, orientin, isovitexin and vitexin have been found to be major flavonoids in the leaves of this plant. Therefore, we had used a two-step method using thin layer chromatography (TLC) and high pressure liquid chromatography (HPLC) for the rapid identification and quantification of the flavones C-glycosides in ethanol extract C. nutans leaves. These results provided useful information for the evaluation of quality of C. nutans raw materials and its commercial products. Moreover, that contributed to the establishment of extract standard from the leaves of C. nutans. The parameters of the ethanol extract of C. nutans leaves were obtained as follows: pH (5,23 ± 0,35), total weight loss due to water (15,62 ± 0,25%), total ash (13,85 ± 0,98%), microbiological limits are achieved the requirement of medicinal standards, content heavy metal and residue of pesticide are not detected. Contents of C-flavones: shaftoside (0,69 ± 0,04 mg/g), orientin (0,24 ± 0,008 mg/g), isovitexin (0,015 ± 0,003 mg/g), vitexin were very low or undetectable.